Here's my proof that \(0=1\).

In which of these steps did I **first** make a flaw in my logic?

**Step 1**: Let's establish the following equations first,
\[ \begin{eqnarray} 0 \times 0 \times 0 \times 0 &=& 0 \\ 0\times 0 \times 0 &=& 0 \end{eqnarray} \]

**Step 2**: Since both these numbers are equal in value, then their ratio is equal to 1.

\[ \dfrac{ 0 \times 0 \times 0 \times 0}{ 0\times 0 \times 0 } = 1 \]

**Step 3**: Cancel out common factors:

\[\begin{eqnarray} \require{cancel} \dfrac{ 0 \times \xcancel0 \times \xcancel0 \times \xcancel0}{ \xcancel0\times \xcancel0 \times \xcancel0 } &=& 1 \\ 0 &=& 1 \end{eqnarray} \]

×

Problem Loading...

Note Loading...

Set Loading...